Comparison of serum levels of Tri‐iodothyronine (T3), Thyroxine (T4), and Thyroid‐Stimulating Hormone (TSH) in preeclampsia and normal pregnancy - Nayereh Khadem; Hossein Ayatollahi; Fatemeh Vahid Roodsari; Sedigheh Ayati; Ehsan Dalili; Masoud Shahabian; Taraneh Mohajeri; Mohamad Taghi Shakeri (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2012)
Background: The physiological changes in thyroid gland during pregnancy have been suggested as one of the pathophysiologic causes of preeclampsia.Objective: The aim of this study was comparison of serum levels of Tri‐iodothyronine (T3), Thyroxine (T4), and Thyroid‐Stimulating Hormone (TSH) in preeclampsia and normal pregnancy. Materials and Methods: In this case‐control study, 40 normal pregnant women and 40 cases of preeclampsia in third trimester of pregnancy were evaluated. They were compared for serum levels of Free T3 (FT3), Free T4 (FT4) and TSH. The data was analyzed by SPSS software with the use of t‐student, Chi‐square, Independent sample T-test and Bivariate correlation test. p≤0.05 was considered statistically significant. Results: The mean age was not statistically different between two groups (p=0.297). No significant difference was observed in terms of parity between two groups (p=0.206). Normal pregnant women were not significantly different from preeclampsia cases in the view of FT3 level (1.38 pg/ml vs. 1.41 pg/ml, p=0.803), FT4 level (0.95 pg/ml vs. 0.96 pg/ml, p=0.834) and TSH level (3.51 μIU/ml vs. 3.10 μIU/ml, p=0.386). Conclusion: The findings of the present study do not support the hypothesis that changes in FT3, FT4 and TSH levels could be possible etiology of preeclampsia